Supplementation strategies to improve efficiency of rumen microbial protein synthesis on cattles fed with tropical grass hay - Marthen L Mullik (Indonesian Center for Animal Research and Development (ICARD), 2006)
This experiment aimed at increasing rumen microbial protein supply into intestine through ration manipulation. Four Santa Gertrudis steers with a mean liveweight (W) of 218 (±5.6) kg were used in a latin square design (4 x 4) to observe the effect of four diets on the efficiency of rumen microbial protein synthesis (EMPS). The steers were given pangola grass hay (8.5% protein) as the basal diet. The treatments were 1) pangola grass hay alone (KON), 2) pangola grass hay + 19 g urea/kg dry matter (DM) hay (URE), 3) as for treatment URE + a supplement mix at 0.5% W (SUP), and 4) as for treatment SUP + salt at 0.15% W (SUG). Urea was added into the hay to support a theoretical EMPS of 160 g MCP/kg digestible organic matter (DOM) whereas supplement mix contains fast, medium, and slow rumen fermentable energy and protein to synchronise energy and protein release in the rumen. Salt was added to alter passage rate of digesta. Addition of urea alone or with supplement mix increased EMPS significantly compared to KON (77 g MCP/kg DOM) but no difference between URE (119 g MCP/kg DOM) and SUP (110 g MCP/kg DOM). Addition of salt into supplement mix increased EMPS by 84% (140 g MCP/kg DOM). It might be concluded that rumen degradable protein (RDP) was deficient in steers fed low quality grass hay hence urea supplementation significantly increased EMPS to a similar extent as that of the supplement mix formulated to have a synchrony in protein and energy release. Increasing fluid dilution rate, by adding salt, also had a dramatic affect on EMPS as observed in treatment SUG. It increased up to the level suggested in the International feeding standards. Key Words: Microbial Protein, Soluble Protein, Dilution Rate, Supplement, Tropical Grass